Textile and clothing design technology - Cassidy, Tom, Professor of design; Goswami, Parikshit (Taylor & Francis, a CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T & F Informa, plc, 2018)
This book will be for designers wishing to improve their technological knowledge, technologists wishing to understand the design process, and anyone else who seeks to work at this design-technology interface. This book will help readers to view technology through the eyes of both the designer and the technologist.